A new species of Bulbophyllum (Orchidaceae; Epidendroideae; Dendrobiinae) from Yunnan, China - Liu, Qiang; Li, Jian-Wu; Jin, Xiao-Hua; Gao, Jiang-Yun (Phytotaxa, 2015)
Bulbophyllum Thouars (1822: 3) is one of the largest orchid genera, including more than 1900 species widely distributed from tropical America, Africa, Madagascar, and mainland Asia to Australasia (Lindley 1830, Pearce & Cribb 2002, Seidenfaden 1979, 1992, Chen et al. 2009, Pridgeon et al. 2014). The species possess a wide range of vegetative form and floral structure (Bose et al. 1980). There are about 103 species (33 endemic) in 18 sections in China (Chen et al. 2009).